International Capacity Cooperation and Financial Support of Countries along the "Chongqing-Xinjiang-Europe" under the background of the Belt and Road - Lin, Chuan; Luo, Jingjing (Archives of Business Research, 2018)
International capacity cooperation is an effective way for Chinese enterprises to further expand the international market under the strategy of the Belt and Road Initiative. In this paper, based on the perspective of policy-oriented finance under the background of "The Belt and Road", and from the perspective of supporting finance, development finance, compensatory finance and welfare finance, the financial support problems in the process of national international production capacity along the “Chongqing-Xinjiang-Europe” are studied. This paper holds that to play the role of financial support, we should base on the national conditions, promote the construction and reform of policy-oriented financial institutions, adhere to the innovation and development of diversified financial support channels, pay attention to practice, establish a comprehensive risk management system, macro-co-ordination, improve the international production capacity cooperation planning.